Bimbingan Belajar di Rumah Menggunakan Alat Peraga Blok Pecahan pada Masa Pandemi Covid 19 - Sofia Sao; Agustina Mei; Ningsih Ningsih; Maria Fatima Mei; Maria Trisna Sero Wondo; Stefania Baptis Seto; Finsensius Yesekiel Naja; Konstantinus Denny Pareira Meke; Grasela Sare Manda (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
The impact of the COVID-19 pandemic is not only on the safety aspect of people's lives but also on the education aspect. One of the problems faced is that students have problems understanding each material given by the teacher because what has experienced so far is that students only get assignments online (What's App, E-Learning), then students do the assignments and send them back. At that moment, there is no direct explanation from the teacher, and each student's answer only relies on the internet (google), even though students need an understanding of the concepts in the material provided, especially mathematics for fractions. One of the activities that help students develop themselves in improving their learning abilities is the tutor. Solution offered to students who live in RT 003, Paupire Village, in this service activity is to provide Student learning assistance and guidance by using fractional block teaching aids during the Covid 19 Pandemic to increase understanding of concepts and learning outcomes. Tutoring can increase students' motivation and academic value, increase understanding of fraction concepts and learning outcomes.